Analisis Menurunnya Perolehan Kursi Caleg Muda di DPRD DKI Jakarta Pada Pemilu Tahun 2024 Dapil Jakarta Selatan - Abdullah, Faris Kamil; Ummah, Aniqotul (Jayapangus Press, 2024)
In the 2024 Indonesian elections, the contest was not only a platform for senior politicians but also an opportunity for young candidates to demonstrate their capabilities. In DKI Jakarta, particularly South Jakarta, there were 78 young legislative candidates. However, despite the surge in young candidates, some members of the public perceived them as mere quota fillers for political parties, lacking political experience. The election results showed that out of 78 young legislative candidates in South Jakarta, only one was elected. This indicates a decline in young candidates' seats compared to the previous period, which had four seats. This study aims to analyze the decline in young legislative candidates' seats in the DKI Jakarta Regional People's Representative Council (DPRD) during the 2024 elections in South Jakarta and gather perspectives from candidates and the public based on voting behavior theory. The research employs a qualitative descriptive method. Data were collected through interviews with several informants, including candidates and South Jakarta residents. The findings reveal that the elected candidate applied an approach aligned with the public's perspective on young candidates. The psychological approach emerged as the most effective strategy in South Jakarta, surpassing the sociological and rational approaches.